Web-Based Employee Work Scheduling Information System Design at PT Trafoindo Power Indonesia - Setiadi, Ade; Effendy, Yusuf; Hidayat, Nur Rahmat; Syamsi, Nur; Rachellya, Lintang Gadis Ratu (Pandawan, 2022)
This study aims to assist PT Trafoindo Power Indonesia in improving the description of the employee work scheduling website. So far, several departments of PT Trafoindo Power Indonesia use an application called Microsoft Excel to process employee work schedules and save a file on a public server where each employee has access to open and perform data engineering. The solution to the indication of the problem is to create a new system design that functions to process data in the form of employee work schedules with a one-way input system. The website is one of the choices that companies need if they want to present information both internal and external. A website would be better if there is a database or what is commonly known as a data warehouse, for the basis of reference for decision-makers tomorrow. In this case, the design of an employee work scheduling information system using Bootstrap as its platform. To obtain the data needed in conducting research, several methods were used, including interviews, observation, and literature study. The data obtained were then analyzed and described using the UML (Unified Modeling Language) method. The final result of the research is the design of a Bootstrap-based employee work scheduling information system using Visual Studio Code as the code editor.